Meat Cultures: Review of Carol J. Adams, Burger and Ted Geier, Meat Markets: The Cultural History of Bloody London - Miller, John MacNeill (Humanimalia, 2021)
Reviewed in this essay: Carol J. Adams, Burger. Object Lessons. London: Bloomsbury Academic, 2018. 192 pp. 13.45 (pb) Ted Geier. Meat Markets: The Cultural History of Bloody London. Edinburgh: Edinburgh University Press, 2017. 200 pp. 110 (hc)